A rare case of bilateral spontaneous tubal ectopic pregnancy - Jahagirdar, Sayali Shripad; Junghare, Pushpa Shankarrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 30 year old woman with 40 days amenorrhoea presented with complains of pain in lower abdomen and blackish discharge per vaginum for 2 days. After investigations and ultrasound, she was diagnosed to have ruptured left tubal ectopic pregnancy. On exploratory laparotomy, patient had ruptured left tubal ectopic pregnancy and unruptured ampullary right tubal ectopic. After appropriate counseling salpingectomy was done on left side and removal of intact ectopic sac by salpingotomy followed by recanalization was done for right tube. Histopathology proved presence of bilateral ectopic pregnancy. Hysterosalpingography done 3 months later confirmed patency of right fallopian tube thus giving hope of natural conception. Spontaneous bilateral ectopic pregnancy is an extremely rare condition which most of the times is not diagnosed preoperatively. Conservative management is possible in a few cases after proper counseling.